Allah speaks to the Prophet Musa - Saniyasnain Khan; Saniyasnain Khan (New Delhi Goodword Kidz, 2003)
A beautifully illustrated children's book that tells the inspiring story of Prophet Musa (Moses) as he receives divine guidance from Allah. The book narrates the momentous event when Allah speaks to Musa from the burning bush, entrusting him with the mission to lead the Israelites out of Egypt. Through simple language and vivid imagery, the story emphasizes themes of faith, trust in Allah, and the importance of fulfilling one's divine purpose, making it an engaging and educational read for young audiences.